The morphology of cyamella and its prevalence in Turkish society - Aksu, F.; Akkoc, R. F.; Bozdag, P. Gundogan (Verduci Publisher, 2023)
- OBJECTIVE: The aim of this study is to determine the prevalence and morphometry of cyamella, one of the sesamoid bones around the knee joint.PATIENTS AND METHODS: In this retrospective study, a total of 9,500 plain/digital radiographs of 6,500 patients
Keywords: Cyamella; Direct X-ray; Sesamoid Bone; Knee Joint